I am inasmuch as I follow the animal. On the human-animal ontological undecidability in Derrida - Firenze, Antonino (Pensamiento. Revista de Investigación e Información Filosófica, 2020)
The aim of this paper is to venture into the ontological undecidability that characterizes the connection between human subjectivity and animal otherness in Derrida’s work L’animal que donc je suis (2006). For that purpose, the paper firstly focuses on the text La Pharmacie de Platon in order to retrace the theoretical premises of this undecidability, highlighting the role played by the scriptural metaphor in the deconstruction of phonologocentric metaphysics carried out by Derrida in this earlier context. Secondly, the paper analyzes the conceptual aporia hidden behind the syntagma L’animal que donc je suis, that enables this posthumous book, namely, to stress the structural semantic undecidability of the «je suis».